Recent Climatic Mass Balance of the Schiaparelli Glacier at the Monte Sarmiento Massif and Reconstruction of Little Ice Age Climate by Simulating Steady-State Glacier Conditions - Weidemann, Stephanie Suzanne; Arigony-Neto, Jorge; Jana, Ricardo; Netto, Guilherme; Gonzalez, Inti; Casassa, Gino; Schneider, Christoph (My University, 2020)
The Cordillera Darwin Icefield loses mass at a similar rate as the Northern and Southern Patagonian Icefields, showing contrasting individual glacier responses, particularly between the north-facing and south-facing glaciers, which are subject to changing climate conditions. Detailed investigations of climatic mass balance processes on recent glacier behavior are not available for glaciers of the Cordillera Darwin Icefield and surrounding icefields. We therefore applied the coupled snow and ice energy and mass balance model in Python (COSIPY) to assess recent surface energy and mass balance variability for the Schiaparelli Glacier at the Monte Sarmiento Massif. We further used COSIPY to simulate steady-state glacier conditions during the Little Ice Age using information of moraine systems and glacier areal extent. The model is driven by downscaled 6-hourly atmospheric data and high resolution precipitation fields, obtained by using an analytical orographic precipitation model. Precipitation and air temperature offsets to present-day climate were considered to reconstruct climatic conditions during the Little Ice Age. A glacier-wide mean annual climatic mass balance of -1.8 +/- 0.36 m w.e. a(-1) was simulated between between April 2000 and March 2017. An air temperature decrease between -0.9 degrees C and -1.7 degrees C in combination with a precipitation offset of up to +60% to recent climate conditions is necessary to simulate steady-state conditions for Schiaparelli Glacier in 1870.
Keywords: monte sarmiento massif; schiaparelli glacier; glacier climatic mass balance; glacier surface energy and mass balance model; little ice age